2021
DOI: 10.1111/ppc.12822
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Turkish version of the Body Understanding Measure for Pregnancy scale (BUMPs)

Abstract: Purpose This study aimed to determine the validity and reliability of the Body Understanding Measure for Pregnancy scale by adapting it to Turkish society. Design and Methods This methodological study was conducted with 265 pregnant women. Findings We performed exploratory factor analysis and determined that the scale consists of 17 items and 2 subdimensions. The two‐factor structure was confirmed as a result of the confirmatory factor analysis. The Cronbach's alpha value of the scale was 0.87. Practise Implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Table 2 presents the characteristics of the 13 selected studies. Regarding location, our results highlight a global concern about the assessment of pregnant women's body image when identifying studies conducted on different continents: North America [24,25], South America [26,27], Europe [3,11,[28][29][30], Asia [31][32][33], and Oceania [34]. The selected articles were from Australia, the United Kingdom (UK), Brazil, Germany, Israel, Japan, Turkey, the United States of America (USA), and Iran, along with a multicenter study that examined pregnant women in the USA and Canada.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Table 2 presents the characteristics of the 13 selected studies. Regarding location, our results highlight a global concern about the assessment of pregnant women's body image when identifying studies conducted on different continents: North America [24,25], South America [26,27], Europe [3,11,[28][29][30], Asia [31][32][33], and Oceania [34]. The selected articles were from Australia, the United Kingdom (UK), Brazil, Germany, Israel, Japan, Turkey, the United States of America (USA), and Iran, along with a multicenter study that examined pregnant women in the USA and Canada.…”
Section: Resultsmentioning
confidence: 68%
“…As a result, we identified 13 studies that met the inclusion criteria and which we subsequently carefully analyzed. We found seven questionnaires that assessed pregnant women's body image [3,[24][25][26]28,31,32], an instrument developed for the adult population and adapted for pregnant women [34], four articles on adapting scales to other cultures [11,27,29,30], and an instrument that assesses body dissatisfaction through a silhouette scale [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KMO test was used to evaluate the suitability of the sample size for factor analysis. If this value is between 0.5 and 1.0, it is acceptable, and below 0.5 indicates that factor analysis is not suitable for the data set [22] , [36] . As a result of the analyzes made for this study, the KMO value in the study was found to be 0.910.…”
Section: Discussionmentioning
confidence: 99%